2015
DOI: 10.1161/jaha.114.001225
|View full text |Cite
|
Sign up to set email alerts
|

Intensive Care Units With Low Versus High Volume of Myocardial Infarction: Clinical Outcomes, Resource Utilization, and Quality Metrics

Abstract: BackgroundThe volume-outcome relationship associated with intensive care unit (ICU) experience with managing acute myocardial infarction (AMI) remains inadequately understood.Methods and ResultsWithin a multicenter clinical ICU database, we identified patients with a primary ICU admission diagnosis of AMI between 2008 and 2010 to evaluate whether annual AMI volume of an individual ICU is associated with mortality, length-of-stay, or quality indicators. Patients were categorized into those treated in ICUs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Lower volume of AMI or HF admissions has previously been associated with worse outcomes, 28,29 and hospitals that used the ICU frequently in the present study tended to have lower annual AMI or HF volume, perhaps utilizing the ICU due to a lack of familiarity in caring for such patients. Furthermore, increased ICU bed availability has been associated with higher ICU admission rates.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Lower volume of AMI or HF admissions has previously been associated with worse outcomes, 28,29 and hospitals that used the ICU frequently in the present study tended to have lower annual AMI or HF volume, perhaps utilizing the ICU due to a lack of familiarity in caring for such patients. Furthermore, increased ICU bed availability has been associated with higher ICU admission rates.…”
Section: Discussionmentioning
confidence: 67%
“…The present study focused on an older population and evaluated associations between ICU admission rates and quality measures. Stolker et al 28 showed that ICUs with low annual AMI volume had higher mortality and provided less evidence-based therapies. Our study looked at a hospital's ICU admission rate and found that hospitals with the highest ICU admission rates had the lowest annual AMI volume.…”
Section: Discussionmentioning
confidence: 99%
“…Though a relationship between volume and outcome has been demonstrated in many conditions, a recent study failed to identify a relationship between ICU MI volume and outcomes. 20 A more selective ICU utilization strategy may be preferable for cost reasons; however, some initially stable patients will ultimately require ICU care, and no risk model has been developed to identify these patients prior to clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study between centers with a low volume versus a high volume of annually treated AMI cases reported significantly lower mortality rates when patients were referred to a high-volume center (11% vs. 4%, p <0.0001 for in-hospital mortality and 7% vs. 3%, p <0.0001 for intensive care unit mortality). 41 These observations are also valid in the case of CS, the most critical condition recorded in a cardiac critical care unit. A statistically significant decrease in overall adjusted mortality was seen in hospitals with high numbers of CS cases.…”
Section: The Level Of Cs Centers and Mortalitymentioning
confidence: 67%